Identifying the Accuracy and Comprehensibility of Students’ English Word By Word Pronunciation at North Lombok Senior High School - Muhamad Irwan; Sudirman Wilian; Arafiq Arafiq; Muhammad Amin (Jurnal Ilmiah Profesi Pendidikan, 2023)
Pronunciation is an important component of language learning that must be well mastered in order to support the development of students' competence in language skills, particularly speaking skills. This descriptive research aims to evaluate the accuracy and comprehensibility of English pronunciation among tenth-grade IPS students consisting of 30 students at SMAN 1 Bayan in North Lombok. Qualitative methods were employed, using student voice recordings as primary data and relevant documents as secondary data. The data analysis technique in this study uses the concept of qualitative data analysis developed by Miles and Huberman in (1994), including data reduction, data display and conclusions drawing. The results showed that while some students demonstrated excellent proficiency in English pronunciation, others faced significant challenges in accurately articulating vowel and consonant sounds. These findings highlight the importance of targeted interventions to support struggling students and improve the pronunciation skills of all students. The research questions are focused on the accuracy and comprehensibility of English pronunciation among students in North Lombok. Through our evaluation, we found that the level of accuracy in common words varied among students, with some struggling to pronounce even basic words accurately.